Analysing the Concepts of Vengeance and Hono(u)r in Shakespeare´s Hamlet and Sumarokov´s Gamlet: A Corpus-based Approach to Literature - Keshabyan, Irina (International Journal of English Studies, 2009)
The present paper aims at carrying out structural and lexical analysis of two contrasting plays –Shakespeare´s Hamlet and Sumarokov´s Gamlet- in a specific linguistic domain. In this contribution, we will attempt to gain some insight into two essential content words: vengeance and hono(u)r, their derivatives and related words, through quantitative analysis of these words and qualitative analysis of their collocates and concordances. Collocational approach will be used to analyse and compare the ways the authors perceive the concepts of vengeance and hono(u)r. In general, the findings will indicate important similarities and/or differences between the structures of the plays per acts and both texts´ basic contents in relation to two important topics -vengeance and hono(u)r.